2007
DOI: 10.1348/135910706x100458
|View full text |Cite
|
Sign up to set email alerts
|

Are beliefs elicited biased by question order? A theory of planned behaviour belief elicitation study about walking in the UK general population

Abstract: TPB belief elicitation studies are not biased by order effects. Interventions to promote walking should consider targeting affective beliefs, e.g. stress relief, in addition to beliefs about health, which is the traditional focus of health campaigns. Given the similarities in beliefs across demographic groups, 'one size fits all' interventions to promote walking are appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…It is possible that individually salient beliefs were affected, but not the five modally salient beliefs we assessed. However, these belief items were derived from a belief elicitation study conducted with a community sample in the same city (Darker et al, 2007a), and these five items covered over 80% (375/466) of the beliefs thereby elicited, so we think this is unlikely. The findings of the present study therefore do not support this part of the proposed causal Psychology and Health 83 pathway of the TPB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that individually salient beliefs were affected, but not the five modally salient beliefs we assessed. However, these belief items were derived from a belief elicitation study conducted with a community sample in the same city (Darker et al, 2007a), and these five items covered over 80% (375/466) of the beliefs thereby elicited, so we think this is unlikely. The findings of the present study therefore do not support this part of the proposed causal Psychology and Health 83 pathway of the TPB.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention itself was developed during an extended period of formative research (described in detail by French, Darker, Eves, & Sniehotta, submitted). This research included a review of TPB walking studies (summarised above) to identify PBC as the construct which should be targeted, a TPB belief elicitation study to identify salient control beliefs (Darker, French, Longdon, Morris, & Eves, 2007a), an interpretative phenomenological analysis on walking behaviour (Darker, Larkin, & French, 2007b), and a piloting of intervention components and TPB measures (Darker & French, submitted).…”
Section: Intervention Development and Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some authors have called attention on the lack of studies in this area (Darker, French, Longdon, Morris & Eves, 2007;Symons-Downs & Hausenblas, 2005). When TPB is used as a reference model in order to promote behavioural change, it is imperative to develop a study to identify beliefs about the target behaviour in the population of interest.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a bid decision (i.e., a "yes, definitely"; "yes, probably"; "no, definitely not"; "no, probably not"; "don't know" decision) to pay an incremental amount to receive a superior hypothetical medication was not affected by the order in which scenarios explaining the superior compared with the inferior medication's properties were presented. Darker, French, Longdon, Morris, and Eves (2007) also found no question order effects in belief elicitation to open-ended questions used in a theory of planned behavior study of walking as exercise. Gold and Barclay (2006) found significant differences resulting from question order in correlations between judgments of one's own risk and of an adverse event occurring (e.g., "What is the chance that you will get into a car accident in the next year?")…”
Section: Health Studiesmentioning
confidence: 88%